Habilidades investigativas del docente universitario: Un estudio en la extensión Cañar, Universidad Católica de Cuenca - Ruiz Alvarado, Priscila Isabel (2016)
This article presents a study about the research skills that professors at “Universidad Católica de Cuenca,” extension in Cañar have. It presents a scope of how research is organized in the university with the specific characteristics the extension in Cañar has. It includes a theoretical review about the topic of ‘skills,’ whose main idea states that in order for an action to require a skill, its performance ought to be exposed to frequency, periodicity, flexibility and complexity. This work explains the results of an exploratory study of an auto-diagnostic kind. In it, the need for training the professors in the university on research skills was determined, making it evident that the most necessary aspects to reinforce were the skills to state scientific problems, to organize the components of the research in stages, and to formulate hypotheses.